Sistem Peringatan Dini Kebakaran Pada Perkebunan Kelapa Sawit Di Lahan Gambut Berbasis Website Dan Telegram - Muhammad Ridwan (Jurnal Rekayasa Proses dan Industri Terapan, 2024)
Peatland is one of the lands that can be planted with oil palm. However, peatlands tend to dry out easily and produce methane gas. If methane gas exceeds the normal limit plus high temperatures it can trigger fires in oil palm plantations on peatlands. As a solution, an early warning system for fires on oil palm plantations on peat lands was built based on a website and telegram. The purpose of this system is to provide information to palm oil farmers regarding changes in methane gas levels and temperature in real time so that they can prevent fires. The components used to build this system are the ESP32 Module to connect the device to the internet, the MQ4 sensor to measure methane gas levels, the DHT11 sensor to measure temperature. The implementation process uses the C programming language to program tools through the Arduino IDE, PHP and MySQL applications to manage the database. Based on the test results, the system displays changes in data on methane gas levels and temperature every 10 seconds via the website and sends a telegram notification if the temperature increases by 1°C or the methane gas is above 1000 ppm. The tool that was built can work optimally at a radius of 15 m from the fire point.